Le role pédagogique du jeu dans l’enseignement du fle : fransızca eğitiminde oyunun eğitsel işlevi - Çelikman, Begüm (My University, 2008)
THE FONCTION OF THE GAMES IN FRENCH LANGUAGE TEACHING This study is preferred due to the fact that the classic methodes in foreign language education in French is impermanent and non-entertaining and therefore is intended to provide a permanent and effective methodes in language teaching through games. The notion of game-playing and the historical development of the games, the types of games used in French lessons, the importance of the games used and its contribution to the students have been examined. In this application how will the games are recognised by the stydents and how they were applied in the classrooms is stated. The observation form, interview and the questionary indicates that the games used in the classic methodes in French education enchaned the utility of the lesson and the interaction between teacher-student, student-student so it is more positive for student for an effective and permanent learning. Key words: Games, Student, Language, Foreign Language, Drama, Enjoyable lesson, French Language Teaching, Methodes, Activity
Keywords: Fransız Dili_Yabancı Dil; Yabancı Dil_Eğitim; Yabancı Dil_Öğrenim ve Öğretim_Fransız Dili